DEFISIENSI VITAMIN B12 DAN GANGGUAN NEUROLOGIS - Dea Muthia Salsabila (Jurnal Medika Hutama, 2020)
The human body stores vitamin B12 for several years. Deficiency of this vitamin is very rare. The elderly are most at risk. However, vitamin B12 deficiency can occur due to not being able to use vitamin B12. The inability to absorb vitamin B12 from the intestinal tract can be caused by a disease known as pernicious anemia. In addition, strict vegetarians or vegans who do not consume the right amount of B12 are also prone to deficiency states. Vitamin B12 is a water-soluble vitamin that is naturally present in some foods, is added to other foods, and is also available as a dietary supplement. Vitamin B12 comes in several forms and contains the mineral cobalt, so compounds with vitamin B12 activity are collectively called "cobalamins". Methylcobalamin and 5 deoxyadenosylcobalamin are forms of vitamin B12 that are active in human metabolism. Some studies reveal that vitamin deficiency occurs mainly due to insufficient food intake resulting in a cluster of neurological symptoms in adults as well as infants. These neurological disorders including apathy, anorexia, irritability, growth retardation, and developmental regression may also involve delayed myelination or demyelination of neurons. It was concluded that vitamin B12 is a micronutrient that is vital for brain health in children, toddlers and the elderly. Various conditions cause B12 deficiency.